Cardiovascular Side Effects of Atomoxetine and Its Interactions with Inhibitors of the Cytochrome P450 System - Pashtoon Murtaza Kasi; Rawad Mounzer; George H. Gleeson (Case Reports in Medicine)
Attention deficit hyperactivity disorder (ADHD) is one of the most common neurobehavioral disorders of childhood and adolescence. Classically, stimulants have been used in the treatment of this condition. Atomoxetine (Strattera; Eli Lilly and Company) is a selective norepinephrine reuptake inhibitor (SNRI), one of the first medications in the nonstimulant class of medications that has been approved by the FDA for the treatment of ADHD. Atomoxetine is a phenoxypropylamine derivative and is structurally related to the antidepressant fluoxetine. The common side effects reported with the use of atomoxetine include mainly GI disturbances. Cardiovascular side effects are less commonly reported. The increase in the noradrenergic tone may explain some of the side effects noted with the use of this medication. Here, we present a case of a patient who presented with syncope, orthostatic hypotension, and tachycardia and discuss the various clinical implications based on the pharmacokinetics and pharmacodynamics of the drug.